Firm size and the division of labor - B. CONTINI (PSL Quarterly Review, 2013)
The recent publication of Italy’s 1981 Industrial Census has highlighted a phenomenon of which there had already been some signs for a number of years - the fact that manufacturing firms in every sector are reducing their size. The data indicate that both the appearance of a large number of small new firms and the reduction in the average number of employees in existing firms of all sizes have contributed to this. Similar conclusions have been drawn for other European countries. The author’s hypothesis is that the observed reduction in the average size of firms is caused by two concurrent factors: (1) the increased rigidity of the overall cost structure of business firms; (2) the increased uncertainty in both factor and product markets, which makes more flexible organisational structures desirable.